Military readiness concepts, choices, consequences - Betts, Richard K. 1947- (Brookings Inst., 1995)
In this book, strategy expert Richard K. Betts surveys problems in developing and measuring combat readiness before, during, and after the cold war. He analyzes why attempts to maximize it often have counterproductive effects, and how confusions in technical concepts cause political controversy